Pengaruh suhu dan lama pemeraman pada inkubator terhadap kualitas fisik kefir - Herly Evanuarini (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2010)
The objective of the research was to find out the optimum temperature and ripening duration in incubator to produce kefir which had physical quality that met the standard of fermented milk quality. The method of experiment was factorial randomized block design. The first factor was temperature that consisted of 25oC, 30oC and 35oC. The second factor was ripening duration that consisted of 12 hours, 18 hours and 24 hours. The result showed that the temperature and duration of ripening gave a highly significant effect (P<0.01) on pH and viscosity. The combination of temperature (30oC) and ripening duration (24 hours) produced kefir which met the standard of Indonesian industry fermented milk such as pH (3.86) and viscosity 157.6 cps. Keywords: Temperature, ripening duration, kefir